Metabolic dynamics of secondary metabolites in Arabica coffee (Coffea arabica): From biosynthesis to post-harvest transformations - Dwitama, Kamilrashid Hadi; Maxiselly, Yudithia; Suherman, Cucu; Rosniawaty, Santi (Kultivasi, 2026)
Coffee (Coffea arabica) is a globally significant beverage whose sensory profile and physiological effects derive from a complex matrix of secondary metabolites. This review presents a comprehensive "lifecycle" perspective of three pivotal classes: the alkaloid caffeine, phenolic chlorogenic acids (CGA), and the diterpenoids cafestol and kahweol. Here, 'lifecycle' defines a metabolite's continuous biochemical trajectory, tracking its genetic origin and ecological function in the plant through structural modifications during fermentation, drying, storage, and roasting. These classes are highlighted because they serve as the primary drivers of bitterness, acidity, and health bioactivities with fundamentally distinct transformational pathways. Following a systematic methodology, this study traces these compounds from biosynthesis to their fate during post-harvest processing. The synthesis reveals that post-harvest interventions cannot create quality but only modulate the bean's inherent chemical potential established by genetics and agronomy. Specifically, fermentation primarily reshapes hydrophilic phenolics (CGA) via hydrolysis to soften astringency, whereas roasting acts as a thermochemical trigger that degrades labile CGA into sensory critical melanoidin precursors and liberates insulated lipophilic diterpenoids. Current literature frequently compartmentalizes pre harvest plant omics and post-harvest food chemistry. This review addresses this gap by integrating these disciplines into a continuous mechanistic model, demonstrating how botanical origins inherently precondition processing outcomes. This holistic perspective offers practical insights for agronomists, processors, and roasters to predict, preserve, and intentionally enhance the sensory and bioactive profile of coffee across the supply chain.